PERTUMBUHAN DAN PERKEMBANGAN ABK - situmorang, puriana; harahap, annisa sari; dalimunthe, rahmah yasrah; Wahyuni, Sri (Thiflun : Jurnal Pendidikan Dasar, 2023)
The purpose of this study is to find out the theory of student development. This type of research is library research. This research makes Library materials as its main data source. Impaired children in society have many terms, teachers generally call children unruly, and are called bad children. Psychologists call children emotionally disturbed or children inhibited emotions. There are many other terms that are often used, generally hinting at the similarity of meaning, namely "unruly children with child delinquency that is not like ordinary children.Â  Children with special needs are children who in the process of growth or development experience physical, mental-intellectual, social or emotional abnormalities or deviations compared to other children their age, so they need special services. Although children are included in the category of children with special needs, they have the same rights as children in general. Children with special needs deserve the same love from both parents, special treatment according to the category they experience, and get a proper education and meet every need. As is known that children with special needs have special needs according to their categories that must be met, either at home or even at school, especially for children with intellectual disabilities.